Perception of female soccer athletes in relation to the practice of the modality in Brazil (Research, Society and Development, 2022)
Because women's soccer still faces many challenges in Brazil, the present study sought to understand the perceptions and perceptions of Brazilian women's soccer athletes about motivation and aspects that favor participation in sports as well as obstacles and challenges that arise with professionalization. Participants consisted of five female athletes aged between 18 and 26 years old (M = 21,01; SD = 2,94) who participated in an interview based on five open-ended questions. By means of content analysis, it has been possible to verify that different challenges are faced, including a lack of support in the field, predominance of machismo, insufficient resources, distance from the family, and gender inequality. They indicated the support of the family nucleus for participation in the modality, and a positive vision of the future, marked by hope in advances related to better conditions of practice and development of the modality, which have been achieved in recent decades.